Peluang Usaha Ekonomi Kreatif Melalui Pemanfaatan Sampah Plastik Sebagai Implementasi Ekonomi Sirkular - Budiarty, Ida; Emalia, Zulfa; Suparta, I Wayan; Nurbety; Darmansyah, Darmansyah (Nemui Nyimah, 2025)
The objectives of this community service activity are: improving the community's economy through creative products from plastic waste processing, providing knowledge and initiation of household waste management into economically useful products. The method used in this activity is a participatory learning model approach. The participatory learning process in this activity is carried out in the form of lectures, discussions and mentoring. Overall, this community service activity has achieved the stated objectives. The Sidodadi Village community is now more empowered in managing plastic waste, and this activity has had a positive impact in improving the economy, knowledge and environmental awareness. Participants do not have adequate skills in processing plastic waste into high-value products. Activity participants do not have good awareness or understanding of the circular economy concept and the importance of waste management. This activity has several important contributions to both village communities and the environment, including reducing plastic waste, implementing a circular economy, increasing community skills, increasing community income, and increasing environmental awareness.